2020
DOI: 10.1111/jbi.13845
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of shell morphology in over‐exploited shellfish reveals adaptive trade‐offs on human‐inhabited islands and incipient selectively driven lineage bifurcation

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…More research is also needed to help interpret the utility of heatmaps for understanding ecological questions related to limpet shell morphology (Bird, 2011;Hamilton et al, 2020). With more robust training datasets per species from multiple populations, age/ size ranges, and habitat types, we may be able use heatmaps to help decipher if and how shell morphology varies intra-specifically over local to regional scales.…”
Section: Future Considerationsmentioning
confidence: 99%
“…More research is also needed to help interpret the utility of heatmaps for understanding ecological questions related to limpet shell morphology (Bird, 2011;Hamilton et al, 2020). With more robust training datasets per species from multiple populations, age/ size ranges, and habitat types, we may be able use heatmaps to help decipher if and how shell morphology varies intra-specifically over local to regional scales.…”
Section: Future Considerationsmentioning
confidence: 99%
“…In our study, PC-P0 resulted non-parallel compared with most sample sites in dorsal view, whilst the same happened with MI in lateral shell view. Hamilton et al (2020) demonstrated that two stressors act as different selective forces moulding the shell of Cellana exarata (Nacellidae). They found phenotypes associated with thermal avoidance in islands without human harvesting, while the prevalence of maladaptive morphotypes for thermal avoidance on islands with high predation pressure suggests that predation is a stronger selective force, driving adaptive trade-offs in shell shape and colour.…”
Section: Potential Forces Driving or Restraining Phenotypic Paralleli...mentioning
confidence: 99%
“…However, it has been argued that parallel phenotypic divergence could be also enhanced or reduced by plasticity (Oke et al, 2016). In consequence, the natural replication of phenotypic divergence across populations provides the opportunity for studying underlying processes of phenotypic evolution and for understanding the roles of natural selection, genetic drift, gene flow and plasticity on the origin of parallel phenotypic divergence (e.g., Westram et al, 2014;Ravinet et al, 2016;Hamilton et al, 2020;Jacobs et al, 2020;Westram et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These attributes have been extensively utilized in ecological and evolutionary research. In the context of bivalves, shell morphology has a notable diversity and complexity, which has been identified as a consequence of adaptive evolutionary processes (Lande and Arnold, 1983;Belonsky and Kennedy, 1988;Hamilton et al, 2020).…”
Section: Introductionmentioning
confidence: 99%